Günəş batereyalarının səmərəliliyinin artırılması üçün mikrokontroller əsasında sensorlu izləyici sistemin işlənməsi - Cabarov, Elvin; Eminov, Seymur; Qurbanov, Azər; Zeynalov, Fuad; Şahquliyeva, Gülgün (My University, 2024)
In the dissertation, various types of solar batteries, their characteristics, advantages, and disadvantages, based on different materials, were analyzed, and high-efficiency solar panels were proposed. Factors affecting the efficiency of solar cells were examined, and methods for mitigating and enhancing these factors were developed. For the sensor-based tracking system, the software of the microcontroller, as well as the remote control and protection system, were developed, considering weather conditions. To improve the efficiency of solar batteries, the schematic of a sensor-based tracking device using a microcontroller was designed, and a prototype of the device was created. Tests and trials were conducted under different weather conditions, and the results were analyzed and recommended for implementation.
Development of a microcontroller-based sensor tracking system to increase the efficiency of solar cells
Keywords: The role of the microcontroller